Cryopreservation of veitchia and howea palm embryos: non-development of the haustorium - Chin, Hoong Fong; Krishnapillay, Baskaran; Alang, Zaleha Christine (CryoLetters LLP, 1988)

(untitled)
Excised embryos of Veitchia and Howea palm seeds can successfully be cryopreserved after desiccating them to a moisture content of around 10%. It was observed that the haustorium in cryopreserved embryos failed to develop, while in the non-cryopreserved embryos at 10% moisture content, the haustorium developed normally. In both cases, plant development appeared normal in culture.